Fun Arabic Teaching With Media Song For Early Child Education School - Yelfi Dewi S; Aliy Rasyid Umar; Ameer Ali Khan; Abd Aziz (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
At this time, the song is also one of the learning methods. This method is usually used for children because, as we know, children are very interested in listening to exciting lessons, especially preschool children. We can also teach children -Children of Arabic through this song method. This study aims to show whether preschool children of Motherland II can learn Arabic using songs. The method used in this study is experimental. While the subjects are children of early childhood education, the results of this study indicate that teachers about learning by using songs can be easily captured by early childhood children but have shortcomings where most children - Early child education Pertiwi II children can memorize quickly, but some children do not know the meaning. Based on this research, it can be concluded that Early Child Education Pertiwi II children can learn Arabic by using songs but still cannot know the meaning perfectly because Children can memorize notes easily but not by understanding the lyrics of each song.